The New Apostolic Reformation : an analysis and critique - Ross, Christopher (Department of Religious Studies, 2014)
Writing in 1999 the eminent Fuller Theological Seminary missiologist, Peter Wagner, claimed that the shape of Protestant Christianity was being changed by the emergence of a new movement that he called the New Apostolic Reformation (hereafter referred to as the NAR). The NAR is a movement that has developed among traditional Pentecostal/Charismatic churches in an attempt to break free from the pressure of denominational structures and influences. One of the key premises of the NAR Movement is that the church must return to the early church's pattern of a five fold ministry as presented in Ephesians 4: 11 because we are living at the end of the current age. The movement calls for the renewal of apostles and prophets to go with the evangelists, pastors and teachers who already exist in many Pentecostal and Charismatic churches. In view of the NAR advocates, this ideal of returning to patterns of New Testament Christianity can only be accomplished by the restoration of the offices of the prophets and the apostles. Proponents of the movement claim that the other three offices, namely, those of the pastor, teacher and evangelist have already been recognised by the church. In the last several years the NAR Movement has emerged in South Africa and has begun recruiting members from traditional Pentecostal and Charismatic churches. Little has been written about this movement in South Africa or its connection to a world widespread of the NAR Movement.